Microbiological Quality Assessment of Date Palm Fruits And Development of a Decontamination Method (Bangladesh Journal of Botany, 2021)
Microbiological quality of four different cultivars (viz., Deglet Noor, Dabbas, Barni and Lulu) of date palm fruits imported into Bangladesh was evaluated. The microbiological quality analysis revealed that the date palm fruit samples are contaminated with bacteria and fungi. Among the studied samples, total aerobic plate count varied from 6.85 ×106 cfu/g to 4.14×107 cfu/g. The maximum bacterial load was observed in 'Dabbas' cultivar and lowest bacteria load was found in 'Lulu' cultivar. The total yeast and mold count ranged from 1.08×103 cfu/g to 6.94 ×104 cfu/g. The maximum yeast and mold count was found in 'Deglet Noor' cultivar whereas this count was lowest in 'Lulu' cultivar. Twenty-two bacterial isolates were randomly selected and identified based on their morphological, cultural and biochemical characteristics. Among the bacterial isolates, Providencia rettgeri was most prevalent (18.18%). The identity of one of the P. rettgeri isolates was confirmed by its 16S rRNA gene sequence comparison and subsequent molecular phylogenetic analysis. The presence of pathogenic bacteria in the imported date palm fruits indicates that they are not suitable for direct human consumption. To improve the microbiological quality of the date palm fruits, several easily available substances were tested as decontaminating agent. The study revealed that commercially available vinegar acts as an excellent decontaminating agent against date palm fruit-associated bacteria.Bangladesh J. Bot. 50(3): 641-649, 2021 (September)